Survival Analysis of Tuberculosis in Children: Environmental and Family Behavior Factors in Medan Tuntungan Subdistrict - Novrika Silalahi; Pitto Pratiwi Malau (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Tuberculosis (TB) in children remains a significant public health issue, particularly in the context of household transmission. This study aimed to analyze the time-to-event of TB incidence among children and to identify environmental and family behavioral factors influencing its occurrence in Medan Tuntungan District, Medan City, in 2025. This study employed an analytical observational design with a retrospective cohort approach and survival analysis. A total of 40 children aged 6–10 years were selected using purposive sampling. Data were analyzed using Kaplan-Meier methods, Log-Rank tests, and Cox proportional hazards regression. The results showed that the median time to TB incidence was 8 months. Significant factors associated with TB incidence in children included exposure to cigarette smoke (HR=3.12; p<0.05), poor household ventilation (HR=2.78; p<0.05), household crowding (HR=2.15; p<0.05), and inadequate family preventive behavior (HR=2.40; p<0.05). In conclusion, environmental and family behavioral factors play a crucial role in determining the timing of TB incidence in children. Survival analysis provides a more comprehensive understanding of risk periods and determinants. TB prevention strategies should focus on improving household environmental conditions and family health behaviors.